2016
DOI: 10.20965/jdr.2016.p0647
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in Tsunami Sediment Transport Modeling

Abstract: Erosion and deposition from tsunamis record information about tsunami hydrodynamics and size that can be interpreted to improve tsunami hazard assessment. We explore sources and methods for quantifying uncertainty in tsunami sediment transport modeling. Uncertainty varies with tsunami, study site, available input data, sediment grain size, and model. Although uncertainty has the potential to be large, published case studies indicate that both forward and inverse tsunami sediment transport models perform well e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Finally, the evaluation of uncertainty in estimation is an essential problem in this research field as pointed out by Jaffe et al (). This study has revealed that the observed thickness and grain size distribution of the tsunami deposits can be reproduced by multiple sets of model input parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the evaluation of uncertainty in estimation is an essential problem in this research field as pointed out by Jaffe et al (). This study has revealed that the observed thickness and grain size distribution of the tsunami deposits can be reproduced by multiple sets of model input parameters.…”
Section: Discussionmentioning
confidence: 99%
“…There are two types of inverse models of the tsunami deposits: the point and 1‐D line models (Jaffe et al, ). Point models such as Moore et al (), Jaffe and Gelfenbaum (), or Naruse et al () consider flow properties from input data of the tsunami deposits at a single location, whereas the 1‐D line models such as Soulsby et al () or Tang and Weiss () reconstruct the behavior of the tsunami from data of the tsunami deposit collected at multiple sampling points on a transect normal to the shoreline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsunami-induced nearshore hydrodynamics tend to be especially chaotic and unpredictable due to the existence of various types of diffusive sources [e.g. bottom boundary shear in Lynett et al (2012), wave breaking in Yoon and Cox (2010), active sedimentation in Cheng and Weiss (2013)], and significant uncertainty remains about sediment processes (Elfrink and Baldock, 2002;Jaffe et al, 2016). Shoreline evolution induced by tsunami waves can have a negative impact on both human structures and marine ecosystems; scouring near coastal structures (Tomita et al, 2006), sediment deposits in harbour basins and navigation channels, beach loss, and loss of habitat for marine species.…”
Section: Introductionmentioning
confidence: 99%
“…This provides important information for inverse/forward modelling which enables the reconstruction of the magnitude of past events (e.g. Jaffe and Gelfenbaum, 2007;Sugawara et al, 2014;Jaffe et al, 2011Jaffe et al, , 2016. However, because the thickness of tsunami sediments can vary significantly (Goto et al, 2011), it is essential to validate whether or not the deposit is a local feature, or if it represents a more ubiquitous event.…”
Section: Introductionmentioning
confidence: 99%